Sitkagranens potentiella merproduktion jämfört med vanlig gran i Hallands län - Bengtsson, Emil; Nilsson, Rasmus (SLU/Dept. of Forest Ecology and Management, 2012)
Sitka spruce (Picea sitchensis) is not considered to be a native species to Swedish forests. It´s origin is the pacific coast of Northern America, an area that is dominated by a coastal climate which makes it likely to believe that it would be well suited for growing in the south-west of Sweden. This study aims to investigate the gain in production that can be reached by growing sitka spruce instead of Norway spruce (Picea abies) in the county of Halland. A regression model based on data from forest experiments was produced to explain the gain in production. This model was based on elevation and annual precipitation.